Застосування системного аналізу в сфері поводження з радіоактивними відходами - Azarov S.I.; Sydorenko V.P.; Zadunay O.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2018)
We substantiated the expediency of using applied systems analysis to study the management of radioactive waste in Ukraine. We adapted the procedures of such analysis and determined the succession of its performing. We present the systemic and structural identification of radiationally dangerous facilities. We also determined the groups of parameters for modeling and defined selected data for their calculation.